INCREASING STUDENT’S ABILITY IN WRITING ARGUMENTATIVE TEXT THROUGH CONTEXTUAL TEACHING AND LEARNING APPROACH (CTL) - larastika indriyhanes; Restu Januarty Hamid; Muliati (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2023)
The purpose of this study was to increasing students’ ability in writing argumentative text in class XI-IPA 4 SMAN 18 Makassar through contextual teaching and learning approach (CTL). This study used the method of qualitative. The research subjects were students of class XI-IPA 4 SMAN 18 Makassar in the odd semester in the academic year 2022/2023 with a sample of 36 students. Data collection is done by giving the task of writing argumentative text. The research data collected through the test showed that the students’ ability in writing argumentative text was increasing through contextual teaching and learning approach. Based on the results of data analysis, it can be seen that the student’s result in pre-test is 51.94 then after getting treatment the students’ post-test increase to 70.56 in pre-test. So, it can be concluded that using the contextual teaching and learning approach can increase students’ ability in writing argumentative text.